2011
DOI: 10.1371/journal.pone.0022527
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Comparative Evolutionary Analysis of Herpes Simplex Virus Type 1 and Varicella Zoster Virus

Abstract: Herpes simplex virus type 1 (HSV-1) and varicella zoster virus (VZV) are closely related viruses causing lifelong infections. They are typically associated with mucocutaneous or skin lesions, but may also cause severe neurological or ophthalmic diseases, possibly due to viral- and/or host-genetic factors. Although these viruses are well characterized, genome-wide evolutionary studies have hitherto only been presented for VZV. Here, we present a genome-wide study on HSV-1. We also compared the evolutionary char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 44 publications
8
87
2
1
Order By: Relevance
“…High‐throughput genome sequencing has provided evidence of recombination between strains in other herpesviruses, namely HSV‐2, VZV, Marek's disease virus, HSV‐1, pseudorabies virus, human cytomegalovirus and infectious laryngotracheitis virus (Hughes & Rivailler, 2007; Kolb, Larsen, Cuellar, & Brandt, 2015; Lee et al., 2013; Norberg et al., 2011, 2015; Sijmons et al., 2015; Szpara et al., 2014; Szpara, Tafuri, et al., 2011; Zell et al., 2012). In the present study, network analysis suggested that recombination has also occurred between EHV‐1 strains.…”
Section: Discussionmentioning
confidence: 99%
“…High‐throughput genome sequencing has provided evidence of recombination between strains in other herpesviruses, namely HSV‐2, VZV, Marek's disease virus, HSV‐1, pseudorabies virus, human cytomegalovirus and infectious laryngotracheitis virus (Hughes & Rivailler, 2007; Kolb, Larsen, Cuellar, & Brandt, 2015; Lee et al., 2013; Norberg et al., 2011, 2015; Sijmons et al., 2015; Szpara et al., 2014; Szpara, Tafuri, et al., 2011; Zell et al., 2012). In the present study, network analysis suggested that recombination has also occurred between EHV‐1 strains.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the divergence in these strains is not immediately obvious. Furthermore, the average divergence for all ORFs was greater for HG52 ILMN than for (30). The analysis involved 37 nucleotide sequences.…”
Section: U S 4 and U S 11)mentioning
confidence: 99%
“…Taken together, the low level of sequence diversity, low rate of recombination, and relative lack of geographic clustering of HSV-2 strains are in contrast to what has been reported for geographically diverse HSV-1 strains. Several studies report that HSV-1 genomes display high levels of DNA diversity, as well as extensive recombination (6,30,31). Furthermore, analysis of genetic distances among HSV-1 strains isolated from Asia, Africa, North America, and Europe shows strong sequence clustering of strains based on geographic location.…”
Section: Figmentioning
confidence: 99%
“…In contrast to both HSV-1 and HSV-2, the related human alphaherpesvirus, varicella-zoster virus (VZV), has relatively low interstrain diversity (12)(13)(14)(15). Decades of research comparing RFLP bands, polypeptide size, and PCR-based sequence analysis have revealed that HSV-1 strains vary between individuals, over sequential isolates from the same individual, and by geographic region (10,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%